THE INFLUENCE OF JOB PROMOTION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT BERKAH CAHAYA IZZAH - Damayanti, Wiwied (JURNAL ASIK, 2024)
The purpose of this study was to determine the influence of Job Promotion and Work Environment on Employee Performance at PT Berkah Cahaya Izzah. The research method used in this study uses a quantitative approach. The population is 41 people. The sampling technique uses saturated samples so that the number of samples in this study is 41 respondents. The data analysis technique uses multiple regression. The results of the study show that: (1) There is a positive and significant influence of the Job Promotion variable on employee performance at PT Berkah Cahaya Izzah. This is evidenced by the tcount > ttable value, namely 9.486 > 2.024 with a probability value (significance) = 0.000, which is below 0.05. (2) There is a positive and significant influence of the Work Environment variable on Employee Performance at PT Berkah Cahaya Izzah. This is evidenced by the tcount > ttable value, namely 6.972 > 2.024 with a probability value (significance) = 0.000, which is below 0.05. (3) There is a positive and significant influence of the variables of Job Promotion and Work Environment together on Employee Performance at PT Berkah Cahaya Izzah. This is proven by the value of Fcount > Ftable, namely 44.937 > 3.24.